Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Pelanggan di Indomaret Hayam Wuruk Purwodadi - Akhmad Nurrofi (Jurnal Ilmiah Aset, 2021)
This study aims to test and analyze the effect of company image, price perception and service quality on consumer satisfaction, case study at Indomaret Minimarket Jl. Hayam Wuruk Purwodadi. Data collection is done through distributing questionnaires to 115 consumers. Data analysis in this study using SPSS version 21. The sampling technique used is the census method and the data testing techniques used in this study include the validity test with factor analysis, test reliability with Cronbach Alpha. Classical assumption tests and multiple linear regression analysis, to test and prove the research hypothesis. The results of the analysis show that the first equation is Y = 0.254X1 + 0.029X2 + 0.551X3 which means the variable company image, service quality has a positive effect on the variable customer satisfaction, while the price perception does not affect consumer satisfaction.